Bilateral valvular involvement in infective endocarditis: A clinically distinct entity? A multicenter retrospective study - Ruchi Bhandari; Nathan L. Maris; Rowida Mohamed (PLoS ONE, 2025)
Background Infective endocarditis (IE), an infection of the cardiac endothelium, is associated with significant morbidity and mortality. IE cases vary substantially based on their valvular involvement, both in terms of risk factors and severity. This study describes patient characteristics and outcomes associated with valvular involvement in IE. Methods Data for this multicenter, retrospective study were obtained from electronic medical chart review of adult patients hospitalized for their index admission for IE between January 2014- January 2018 in the Appalachian region, USA. Descriptive summary statistics are presented by valvular involvement: (1) Left-sided Infective Endocarditis (LSIE): aortic/mitral valve; (2) Right-sided Infective Endocarditis (RSIE): tricuspid/pulmonary valve; and (3) Bilateral Infective Endocarditis (BLIE): right and left-sided. Multivariable logistic regression analysis examined the association of valvular involvement with intensive care unit (ICU) admission. Results Overall, 726 patients with IE were included in this retrospective study that provides a novel analysis of IE valvular involvement, highlighting how patient characteristics, comorbidities, substance use behaviors, and clinical outcomes differ across LSIE, RSIE, and BLIE presentations. Drug use, the presence of one or two comorbidities, and bilateral or left-sided valve involvement were independently associated with increased odds of ICU admission. Notably, patients with BLIE experienced a greater clinical burden, requiring more frequent specialist consultations, increased use of pain management services, higher mortality, and a higher rate of surgical interventions. Conclusion BLIE represents a clinically distinct IE subgroup characterized by dual vulnerabilities: high-risk substance use behaviors associated with RSIE, and medical complexity typically seen in LSIE. Our findings underscore the importance of including BLIE as a distinct category in future epidemiological and clinical investigations of endocarditis valvular involvement.